Hubungan Terapi Non Farmakologi terhadap Ganguan Tidur pada Lansia di Desa Sukahurip - Oktaviani, Mayang; Chalid, Desridius (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT  Elderly is a group that has experienced setbacks in psychological and physiological aspects. Everyone will experience old age, so this stage is a natural and natural stage at the end of the human life phase. The World Health Organization (WHO) categorizes the age limit for the elderly. To determine the effect of non-pharmacological therapy on sleep disturbances in the elderly in Sukahurip village in 2023. This research uses a type of quantitative research with a research design study using a quasi-experiment with a pretest-posttest control group design approach. In this study there was one group of subjects where the group was observed before the intervention was carried out and then observed again after the intervention. The results of this research were that of the total male and female respondents who had the highest score of experiencing sleep disturbances, there were 16 women (53.3%), and the age of the respondents who experienced the highest sleep disturbance in the elderly in Sukahurip village, namely the elderly aged 60 -69 years as many as 21 respondents out of a total of 30 respondents. Where some of the respondents who have jobs include retirees, farmers, employees and housewives who have the highest number of respondents who experience sleep disturbance problems, namely farmers as many as 12 (40%) results of the "Test Statistics", known Asymp. Sig. (2-tailed) is worth 0.000. p-value 0.000 <0.05. Respondents can know that there is an influence of the application of non-pharmacological therapy on sleep disorders, so that with this research they can add knowledge and insight to be able to reduce the problem of sleep disorders in the elderly with non-pharmacological therapy. And this research can be used as a reference for future researchers Keywords: Non-Pharmacological Therapy, Sleep Hygiene, Warm Water Foot Soaking Therapy and Sleep Disturbances In The Elderly  ABSTRAK Lansia  merupakan  kelompok  yang  telah  mengalami  kemunduran  dalam  aspek  psikologis  maupun  fisiologis. Setiap  orang  akan  mengalami  lanjut  usia,  sehingga  tahapan  ini  merupakan tahapan  yang  wajar  dan  alami diakhir fase  hidup  manusia.World  Health  Organization (WHO) mengkategorikan batasan umur lansia  yaitu  usia  pertengahan  usia  45-59 tahun, lanjut usia pertama yakni usia 60-74 tahun, lanjut usia tua yakni 75-90 tahun,  dan  sangat  tua  yakni  >90  tahun (Widyaningrum et al., 2019). Mengetahui pengaruh terapi non farmakologi terhadap gangguan tidur pada lansia di desa sukahurip tahun 2023.  Penelitian ini menggunakan jenis penelitian kuantitatif  dengan study Desain penelitian menggunakan Quasi experiment dengan pendekatan Pretest-Posttest Control Group Design. Pada penelitian ini terdapat satu kelompok subjek dimana kelompok tersebut di observasi sebelum dilakukan intervensi kemudian diobservasi lagi sesudah intervensi. hasil penilitian ini dari total responden berjenis kelamin laki-laki dan perempuan yang memiliki nilai tertinggi mengalami gangguan tidur adalah perempuan sebanyak 16 (53,3%), dan usia responden yang peling tinggi mengalami gangguan tidur pada lansia di desa sukahurip yaitu lansia yang berusia 60-69 tahun sebanyak 21 responden dari total 30 responden. Dimana sebagian responden yang memiliki pekerjaan diantaranya pensiunan,petani,karyawan dan IRT yang memiliki jumlah responden tertinggi yang mengalami masalah gangguan tidur yaitu petani sebanyak 12 (40%)hasil “Test Statistik”, diketahui Asymp. Sig. (2-tailed) bernilai 0,000. nilai p value 0,000 < 0,05. Responden dapat mengetahui bahwa adanya pengaruh penerapan terapi non farmakologi terhadap gangguan tidur,sehingga dengan adanya penelitian ini dapat menambah pengetahuan dan wawasan agar mampu mengurangi masalah gangguan tidur pada lansia dengan terapi non farmakologi Dan penelitian ini bisa dijadikan sebagai referensi bagi peneliti selanjutnya Kata Kunci : Terapi Nonfarmakologi,Sleep Hygine,Terapi Merendam Kaki dengan Air Hangat dan Gangguan Tidur Pada Lansia